Sense of community through neighborhood center - Farkisch .N,; Che-Ani .A.I,; Ahmadi .V,; Surat .M,; Tahir .M.M, (Penerbit UKM, 2011)
Understand and perception of place happened due to connection between Humans and their surrounding environment. In this study, feature of a neighborhood center as community is considered as the base of research. Against conducted researches just through attention to physical factors cannot achieve to cohesion and sense of place. In this paper argued that physical place affected by social relations of people. People’s activities also are effective in their environmental perception. For recognizing the sense of place dimension have reviewed argument and results of scholars. In this paper analyzed researches that have done, to some extent. Furthermore, in the important part of those researches Sense of place has three